'It's not for people like (them)': structural and cultural barriers to children and young people engaging with nature outside schooling. Issue 1 (2nd January 2023) - Waite, Sue; Husain, Fatima; Scandone, Berenice; Forsyth, Emma; Piggott, Hannah
ABSTRACT: The UK Department for the Environment, Food and Rural Affairs (DEFRA) commissioned research into provision of opportunities that support children and young people's (CYP) engagement with natural environments outside school time to identify whether CYP from disadvantaged backgrounds access the opportunities available, the challenges to do so, and how provision might be optimised to improve engagement. We used mixed methods, including document review, interviews with national stakeholders, survey of local provision and local case studies with provider interviews and focus groups with CYP. We identified four categories of engagement: outdoor learning; play; improving the natural environment; sports and exercise, and three main provider types: environmental organizations; community groups; and adventure and residential education providers. Using conceptual frames of habitus and 'nature capital', we reflect on barriers that currently limit inclusive youth engagement with nature outside schooltime and suggest implications for the design of future opportunities.